2016
DOI: 10.1111/hae.12913
|View full text |Cite
|
Sign up to set email alerts
|

Penny wise, pound foolish: an assessment of Canadian Hemophilia/inherited bleeding disorder comprehensive care program services and resources

Abstract: Under-funding of programmes and suboptimal monitoring of valuable clotting factor concentrate utilization and reporting are both 'penny-wise' and 'pound-foolish'. A formal accreditation process is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
2
9
0
Order By: Relevance
“…Interestingly, while a Delphi survey of healthcare providers and patients/parents with juvenile idiopathic arthritis (JIA) established that addressing psychosocial, educational and vocational needs constitute best practice and are deemed highly feasible in most centres in the United Kingdom, our survey revealed high importance but low feasibility in the Canadian HTC . This is echoed by a recent audit by the CHS that identified serious human resource deficiencies in most Canadian HTCs, especially physiotherapists and social workers . Similar to our survey results, the UK Delphi study also revealed limited feasibility of transitional care being provided by professionals who are knowledgeable about adolescent development …”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Interestingly, while a Delphi survey of healthcare providers and patients/parents with juvenile idiopathic arthritis (JIA) established that addressing psychosocial, educational and vocational needs constitute best practice and are deemed highly feasible in most centres in the United Kingdom, our survey revealed high importance but low feasibility in the Canadian HTC . This is echoed by a recent audit by the CHS that identified serious human resource deficiencies in most Canadian HTCs, especially physiotherapists and social workers . Similar to our survey results, the UK Delphi study also revealed limited feasibility of transitional care being provided by professionals who are knowledgeable about adolescent development …”
Section: Discussionsupporting
confidence: 77%
“…United Kingdom, our survey revealed high importance but low feasibility in the Canadian HTC. 17 This is echoed by a recent audit by the CHS that identified serious human resource deficiencies in most Canadian HTCs, especially physiotherapists and social workers 18. Similar to our survey results, the UK Delphi study also revealed limited feasibility of transitional care being provided by professionals who are knowledgeable about adolescent development 17.…”
supporting
confidence: 81%
“…Differing healthcare reimbursement systems, budgetary constraints, and geographical and cultural factors, make it difficult for any country to fully deliver ideal care. Some regions, mainly developed countries, may have sufficient treatment product available but then have a higher expectation of outcomes and often insufficient supportive care experience and personnel to monitor adherence and outcomes and implement regular follow-up [8]. In contrast, developing regions may not have ready access to factor replacement but have developed excellent physiotherapy and rehabilitation programs.…”
Section: Coagulation Disorders;mentioning
confidence: 99%
“…Coagulation disorders include many chronic conditions that require life‐long treatments to reduce risk of hemorrhage (bleeding disorders) or of blood clotting. A multidisciplinary, approach to patients with bleeding and clotting disorders has been shown to improve clinical outcomes, decrease mortality rates, and improve cost‐effectiveness in health care settings . Nurses play a crucial role as part of the multidisciplinary team providing care to these patients.…”
Section: Introductionmentioning
confidence: 99%
“…A multidisciplinary, approach to patients with bleeding and clotting disorders has been shown to improve clinical outcomes, decrease mortality rates, and improve costeffectiveness in health care settings. [1][2][3] Nurses play a crucial role as part of the multidisciplinary team providing care to these patients.…”
Section: Introductionmentioning
confidence: 99%